Diagnosis and proposals for construction of a sports security in Argentina (Impetus, 2021)
Who elaborated this diagnosis and proposals we have maintained, for more than ten years, practices of scientific research within the framework of public universities and state agencies such as CONICET. Those research has produced novel knowledge –Punched in articles, forums, doctoral theses and books – 1on some of the sectors involved in the issue that summons us: fan groups, the media, security agencies, among others.